Search 82,200 tutors
FIND TUTORS
Ask a question
0 0

Simplify 3(2x^-1y^5)^-2

Tutors, please sign in to answer this question.

1 Answer

Let’s do a similar problem:

E = 11 ( 2 a^3 b^(-5) )^(-7)

I spread the numbers apart for visibility, but multiplication is still assumed because there is no arithmetic operator symbol shown.

We know (x y^q )^p = x^p y^(pq), so:

E = 11 2^(-7) a^((3)(-7)) b^((-5)(-7))

E = 11 2^(-7) a^(–21) b^(35)

We know x^(-3) = 1/(x^3), so:

E = 11 (1/2^7) (1/a^21) b^35

E = 11 b^35 / (128 a^21)